2014
DOI: 10.17105/spr-13-0052.1
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Attributes of Adequate and Inadequate Responders to Reading Intervention in Middle School

Abstract: No studies have investigated the cognitive attributes of middle school students who are adequate and inadequate responders to Tier 2 reading intervention. We compared students in Grades 6 and 7 representing groups of adequate responders (n = 77) and inadequate responders who fell below criteria in (a) comprehension (n = 54); (b) fluency (n = 45); and (c) decoding, fluency, and comprehension (DFC; n = 45). These students received measures of phonological awareness, listening comprehension, rapid naming, process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
35
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(41 citation statements)
references
References 43 publications
4
35
2
Order By: Relevance
“…Similarly, Miciak et al (2014a) Results indicated a clear hierarchy on both cognitive and academic variables, with the adequate responder group scoring highest on academic and cognitive variables, the groups with specific reading deficits (comprehension or fluency) scoring similarly, and the globally impaired group scoring lowest on both cognitive and academic measures. In both of the above studies, the differences in level observed on cognitive and academic variables between adequate and inadequate responders parallel differences in readings skill, consistent with a continuum of severity hypothesis.…”
Section: Validity Of Intervention Response As An Attribute Of Ldmentioning
confidence: 82%
See 3 more Smart Citations
“…Similarly, Miciak et al (2014a) Results indicated a clear hierarchy on both cognitive and academic variables, with the adequate responder group scoring highest on academic and cognitive variables, the groups with specific reading deficits (comprehension or fluency) scoring similarly, and the globally impaired group scoring lowest on both cognitive and academic measures. In both of the above studies, the differences in level observed on cognitive and academic variables between adequate and inadequate responders parallel differences in readings skill, consistent with a continuum of severity hypothesis.…”
Section: Validity Of Intervention Response As An Attribute Of Ldmentioning
confidence: 82%
“…This is most clearly illustrated in population studies of academic achievement, in which student performance in reading and mathematics are normally distributed (Jorm et al 1986;Rodgers 1983;Shaywitz et al 1992;Silva et al 1985). In recent years, large-scale studies investigating response to reading intervention have further supported the dimensional nature of attributes of LD, as individual instructional response is continuously distributed, without naturally occurring demarcations of qualitatively different groups Miciak et al 2014a;Vellutino et al 2006). Further, studies applying methods from behavioral genetics have failed to identify qualitatively different genetic constellations associated with the heritability of reading and mathematical disorders (Fisher and DeFries 2002;Grigorenko 2001Grigorenko , 2005Plomin and Kovas 2005).…”
Section: The Attributes Of Lds Are Dimensional Not Categoricalmentioning
confidence: 98%
See 2 more Smart Citations
“…Within these interventions there are subgroups of students who are considered high responders particularly when the intervention has been intensive. Also, there is a subset of struggling readers who continue to struggle even after receiving intensive instructional support (e.g., Miciak et al, 2014). This latter group is often described as “inadequate responders.” The purpose of this study was to examine the cognitive attributes, attention problems, and self-efficacy of adequate and inadequate responders to intensive reading intervention.…”
mentioning
confidence: 99%